2014
DOI: 10.1001/jamaneurol.2013.5378
|View full text |Cite
|
Sign up to set email alerts
|

Variant Creutzfeldt-Jakob Disease With Extremely Low Lymphoreticular Deposition of Prion Protein

Abstract: IMPORTANCE Human transmission of bovine spongiform encephalopathy causes the fatal neurodegenerative condition variant Creutzfeldt-Jakob disease (vCJD) and, based on recent human prevalence studies, significant subclinical prion infection of the UK population. To date, all clinical cases have been fatal, totaling 228 mostly young adults residing in the United Kingdom. OBSERVATIONS Here we describe the investigation and case history of a patient recently diagnosed as having vCJD in the United Kingdom. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Indeed, all biopsies of donor primates but one were negative, and one of those donor primates (Macaque D) developed vCJD without detectable peripheral PrPres despite an IV injection. Those observations are in agreement with the publication of Mead and colleagues 24 describing a vCJD patient with close to undetectable peripheral PrPres accumulation.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, all biopsies of donor primates but one were negative, and one of those donor primates (Macaque D) developed vCJD without detectable peripheral PrPres despite an IV injection. Those observations are in agreement with the publication of Mead and colleagues 24 describing a vCJD patient with close to undetectable peripheral PrPres accumulation.…”
Section: Discussionsupporting
confidence: 93%
“…However about a third of the vCJD blood samples tested so far were score negative (6 out the 21 vCJD affected cases) [26], [55], [56]. The idea of a lower/absence of prionemia in certain vCJD cases is also indirectly supported by the observations recently reported by Mead et al This author reported that in a vCJD affected patient that was negative using the MRC vCJD blood detection assay, the lympho-reticular tissues displayed unusually low PrP Sc accumulation levels [57]. Beyond this, a low level or an absence of infectivity in the blood of certain vCJD infected patients could also explain the lack of disease transmission observed so far in certain patients who received blood from donors who later developed vCJD [58].…”
Section: Discussionmentioning
confidence: 80%
“…4) and DWI sequences in over 90% of cases. Tonsil biopsy shows immunostaining and deposition of type 2B or type 4 PrP res in the majority of cases, 95,96 but this test is invasive, and definitive diagnosis rests on neuropathological examination of brain tissue, usually at post-mortem.…”
Section: Diagnostics and Treatmentmentioning
confidence: 99%